Application for Submission of Research Recommendations and Practice Work Web Based (Buana Information Technology and Computer Sciences (BIT and CS), 2021)
Application Submission of Recommendations for Research and Job Training which is often late hampers students who will carry out Research and Practical Work activities that will be carried out at institutions in Karawang, making students have to spend time visiting the Kesbangpol office where sometimes the completion of the letter is not clear when the completion completed, and also because of the head of the Office's signature problem. The research method used is to use the Waterfall method which in this method includes needs analysis, design, implementation, verification, and maintenance. Therefore it is hoped that after the design and recommendation system of a recommendation letter system/tools proposed by the author, it is useful for efficient time for students who will submit a recommendation letter for research and practical work to agencies in Karawang Regency and students do not have to go directly to the Kesbangpol office. Karawang Regency to submit a recommendation letter